(untitled) (Journal of the College of Education for Women, 2020)
The study aims at evaluating the penalty of semi- intentional killing felony in the Egyptian and Algerian criminal law following the Islamic Law (Shari’a). The study used the descriptive, evalutive and analytical methodology to reach the topic in question. To meet the theoretical significance of the study, much data has been collected to give a comprehensive picture about the topic under examination. As for the practical significance of the study, it helps the juridical power to reconsider and phrase the legal materials of the semi-intentional killing penalty based on the Islamic law. The study has come to the conclusions that the Islamic Law (Shari’a) imposes a compensation (blood-money) to be given to the deceased family and an act of expiation as a penalty against those who proved committed of intentional killing felony. However, the Egyptian Penal Law imposes hard labor/imprisonment as an alternative penalty against this felony. On the other hand, the Algerian Criminal law imposes imprisonment as an alternative penalty to this felony. Consequently, the penalties prescribed by both Egyptian and Algerian Laws contradict with what Islamic Law (Shari’a) necessitates. The study recommended that the Egyptian and the Algerian Criminal laws to activate the Islamic law represented by the compensation (blood-money) and act of expiation as a penalty to this crime.